Exploring neuromarketing strategies towards boosting consumer engagement with rural agricultural products: A systematic review - Olaitan Ayotunde Shemfe; Ifeanyi Mbukanma (Interdisciplinary Journal of Management Sciences)
Rural agricultural products play a crucial role in local economies and cultural heritage; however, they encounter significant market challenges, such as limited consumer trust, weak branding, and inadequate marketing resources. Neuromarketing, which involves the application of neuroscience tools such as eye-tracking, electroencephalogram (EEG), functional magnetic resonance imaging (fMRI), and functional near-infrared spectroscopy (fNIRS), provides a novel approach to understanding consumers' unconscious responses to marketing stimuli. This systematic review synthesises the literature on neuromarketing strategies designed to enhance consumer engagement with rural agricultural products. Multiple searches were conducted across various academic databases (e.g., Google Scholar, ScienceDirect, PubMed, PsycINFO, JSTOR, AGRIS) using targeted keywords (e.g., "consumer neuroscience," "rural agricultural products," "sensory marketing"), focusing on peer-reviewed English studies published from 2018 onwards. From an initial pool of 236 articles, screening and eligibility checks yielded 14 highly relevant studies. Key themes that emerged include the influence of emotional and cognitive stimuli, packaging design, narrative storytelling, labelling, pricing, and ethical cues on consumer behaviour. For instance, appealing emotional narratives and authentic cultural storytelling consistently enhance recall and brand loyalty. Clear, trust-building labels (e.g., "organic," "antibiotic-free") engage decision-making regions of the brain, serving as cognitive shortcuts that strengthen perceived value. Additionally, visual design elements such as prominent eco-labels and origin indicators capture attention and convey quality. Despite their value, existing studies face key limitations such as small, non-representative samples and artificial settings. However, applying neuroscience insights can help rural producers enhance packaging, branding, and storytelling to build consumer trust and promote sustainable economic growth.